The interaction of enteric bacterial effectors with the host engulfment pathway control innate immune responses. (1st January 2021) - Sayed, Ibrahim M; Ibeawuchi, Stella-Rita; Lie, Dominique; Anandachar, Mahitha Shree; Pranadinata, Rama; Raffatellu, Manuela; Das, Soumita
ABSTRACT: Host engulfment protein ELMO1 generates intestinal inflammation following internalization of enteric bacteria. In Shigella, bacterial effector IpgB1 interacts with ELMO1 and promotes bacterial invasion. IpgB1 belongs to the WxxxE effector family, a motif found in several effectors of enteric pathogens. Here, we have studied the role of WxxxE effectors, with emphasis on Salmonella SifA and whether it interacts with ELMO1 to regulate inflammation. In-silico-analysis of WxxxE effectors was performed using BLAST search and Clustal W program. The interaction of ELMO1 with SifA was assessed by GST pulldown assay and co-immunoprecipitation. ELMO1 knockout mice, and ELMO1-depleted murine macrophage J774 cell lines were challenged with WT and SifA mutant Salmonella . Bacterial effectors containing the WxxxE motif were transfected in WT and ELMO1-depleted J774 cells to assess the inflammatory cytokines. ELMO1 generates differential pro-inflammatory cytokines between pathogenic and nonpathogenic bacteria. WxxxE motif is present in pathogens and in the TIR domain of host proteins. The C-terminal part of ELMO1 interacts with SifA where WxxxE motif is important for interaction. ELMO1–SifA interaction affects bacterial colonization, dissemination, and inflammatory cytokines in vivo . Moreover, ELMO1–SifA interaction increases TNF-α and IL-6 production from the macrophage cell line and is associated with enhanced Rac1 activity. ELMO1 also interacts with WxxxE effectors IpgB1, IpgB2, and Map and induces inflammation after challenge with microbes or microbial ligands. ELMO1 generates a differential response through interaction with the WxxxE motif, which is absent in commensals. ELMO1-WxxxE interaction plays a role in bacterial pathogenesis and induction of inflammatory response.